Релігійні потреби віруючого: до постановки питання - Кулагіна, Г. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2009)
In this article author said about some scientific points of view about religion requirements of the believers. The main idea is about that religion requirements of the believers corresponded to spiritual sphere and caused social motives.